Avaliação de implementação do programa de Educação Especial de São Paulo em uma Escola Municipal - Rodrigues, Cristiane de Oliveira Figueiredo (2020)
This research aimed to evaluate the implementation of the special education program of the city of São Paulo in a municipal elementary school. The Paulistana Special Education Policy, from the perspective of Inclusive Education, governed by Decree nº 57.379 / 2016 and Ordinance nº 8.764 / 2016, came into force in 2017. It is worth checking how it was implemented in the selected educational unit. A study of the history of special education was carried out, seeking to conceptualize this type of teaching and to present its history in the country from the point of view of legislation, addressing and differentiating the paradigms of integration and inclusion. The theoretical framework was built around the fundamentals of program evaluation, presenting essential concepts to understand it, as well as situating, in the policy cycle, the approach chosen for evaluation, which is implementation, in addition to portraying its fundamentals. The analysis methodology is, primarily, qualitative. First, a description of the legal documents, which are the National Policy for Special Education, in the Inclusive Perspective, as well as the decree and ordinance that regulate the program in the municipality, are carried out. Then, it is evaluated how the implementation of this program occurred, based on the information received through observation, questionnaires and interviews, within the selected EMEF. There were three levels of investigation: equipment, human resources and services. The results presented show that the program was implemented in the analyzed school, and in the equipment axis it is observed effectiveness in the implementation. In the areas of services and human resources, it was found that there was the implementation of most of the demands involved, but with some cracks, because there are impasses and challenges to be met, with emphasis on continuing education, the difficulty of talking to the family and health services, the reduced number of professionals in the support service